New mitochondrial and nuclear primers for the Mediterranean marine bivalve Pinna nobilis - SANNA, D.; DEDOLA, G.L.; SCARPA, F.; LAI, T.; COSSU, P.; CURINI-GALLETTI, M.; FRANCALACCI, P.; CASU, M. (Mediterranean Marine Science, 2014)
Pinna nobilis is the largest endemic Mediterranean marine bivalve. During past centuries, various human activities led to the regression of its populations. As a consequence of stringent standards of protection, demographic expansions are currently reported in many sites. We designed a set of four mitochondrial- and two nuclear- specific PCR-primers with the aim to provide molecular tools to gather new insights into the genetic variability of this species. A total of 54 specimens were sampled from 25 Mediterranean localities in order to evaluate the level of polymorphism of these markers in P. nobilis. The most variable molecular markers identified were the mitochondrial Cytochrome c Oxidase subunit I (COI), NADH dehydrogenase subunit 3 (nad3), and 16S ribosomal DNA (16S). Positive results, in terms of good amplifications and scorable sequences, were also obtained in the co-generic Pinna rudis. The molecular markers identified in this study, and the PCR-protocols provided, represent a useful tool for future researches devoted to infer the genetic variability of P. nobilis populations thus allowing the development of effective conservation measures.